Key Drivers of Product and Service Innovation in - Coetzee, Charl Dominic (My University, 2011)
Innovation is internationally recognized as an important source of competitive advantage. It was the aim of this research to isolate which factors play a key role within South African firms in unlocking their product and service innovation ability, and in so doing potentially promote prosperity for firms individually and for the country as a whole. Six factors were posited as propositions on the basis of what crystallized out of the literature review. A survey was distributed in electronic format to senior managers in 70 firms and the respondents were asked to rate 29 statements on a 5 point Likert scale. Factor analysis was conducted on the data collected in order to establish what the key drivers of innovation are. Although the factor analysis which was conducted did not clearly point to the six propositions initially identified, generalized groupings of questions pertaining to the six propositions were isolated. The study does serve to confirm the existence of each of the propositions as drivers of product and service innovation in South African firms.
MBA - WBS
Keywords: Product innovation; Service innovation; Innovation